Cutaneous haemangioendothelioma: a possible link with chronic exposure to vinyl chloride. Issue 1 (January 1990) - Davies, M F; Curtis, M; Howat, J M
Abstract : A patient who worked with polyvinyl chloride developed a malignant haemangioendothelioma of a toe. This rare tumour is more commonly found in the liver where it has been reported to arise in association with exposure to the vinyl chloride monomer.